Integrasi Artificial Intelligence dalam Manajemen Strategi Syariah untuk Meningkatkan Keunggulan Kompetitif Organisasi - Sunarto; Muhardi; Tasya Aspiranti; Sri Suwarsi; Ima Amalia; A. Harits Nu'man (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the integration of Artificial Intelligence (AI) in sharia strategic management and its impact on organizational competitive advantage. The research method used is a literature review with a descriptive qualitative approach. Data were collected through a systematic search of reputable national and international journal articles published between 2022 and 2026, focusing on the themes of AI, strategic management, sharia-based organizations, and competitive advantage. Selected articles were then analyzed using content analysis techniques to identify patterns, key concepts, and the relationship between AI capabilities, sharia principles, and strategic management practices. The analysis results were synthesized thematically to formulate research findings and develop a relevant conceptual model. The findings indicate that AI integration can improve the effectiveness of strategic decision-making, operational efficiency, sharia compliance, service innovation, and the organization's ability to respond to the dynamics of the business environment. However, AI implementation needs to be supported by strong sharia governance, ethical data use, and human resource competency development. This research offers a conceptual model of AI-Driven Sharia Strategic Management as an integrative framework that connects AI capabilities, sharia values, and organizational competitive advantage, and provides theoretical and practical contributions to the development of sharia strategic management in the digital era.